Evaluating Cybercrime as a Violation of IT Professional Ethics: A Case Study Analysis of the 2020–2025 Ransomware Attacks - Luh Putu Cintya Karmayanti; Kadek Agus Raditya Adi Dharma; Ida Bagus Alit Sukabawa; Ida Bagus Nyoman Mahadivya Sutha; Lalu Ginandjar Hendru Alamsyah (Journal of Digital Law and Policy, 2026)
Ransomware attacks are a form of cybercrime that has seen a significant increase during the digital transformation era, causing serious impacts on information system security, service continuity, and public interests. This research aims to evaluate cybercrime as a violation of the professional code of ethics for information technology thru a case study analysis of ransomware attacks that occurred between 2020 and 2025. This research employs a descriptive qualitative approach with literature review and document analysis methods, encompassing scientific publications, cybersecurity reports, policy documents, and professional codes of ethics for information technology. The research results indicate that many ransomware attacks are closely related to weak information system security governance, professional negligence, and a lack of competence and ethical awareness in system management. This condition reflects a violation of the core principles of the information technology professional code of ethics, specifically the principles of responsibility, professional competence, integrity, and protection of public interest. Additionally, an analysis of the national cybersecurity landscape thru the National Cyber Security Index (NCSI) indicates that despite an increase in Indonesia's score and ranking in 2023, strengthening technical aspects must be balanced with consistent ethical and professional practices at both the individual and organizational levels. This research concludes that preventing and mitigating ransomware attacks cannot rely solely on technical solutions, but requires integration between system security governance, professional competence enhancement, and adherence to the professional code of ethics for information technology to support cyber resilience and safe and sustainable digital transformation.